Improving the work-integrated learning experience through a third-party advisory service - Jackson, D.; Ferns, Sonia; Rowbottom, D.; Mclaren, D. (Australian Vocational Education and Training Research Association, 2016)
This study trialled a Work-Integrated Learning (WIL) Advisory Service, provided by the Chamber of Commerce and Industry of Western Australia (CCIWA) in collaboration with four WA universities. The service was established to broker relationships between industry and universities, support employers engaged in WIL and enhance the WIL experience for both students and employers. It was implemented over a 10-month period, covering two academic semesters, during 2015. Forty-six student work placements were conducted through the service simultaneously with an extensive promotional campaign to raise awareness of the benefits of WIL among local employers. Data were gathered from participating employers and students to evaluate the service and measure its success. Strategies to improve the service and to better manage issues arising during the WIL process are discussed. The study highlights the potential benefits of associations and third parties in nurturing collaborative partnerships between industry and universities for the purposes of WIL and improving graduate performance.